If 3n=3a-6 than the answer is B
Answer:
D?
Step-by-step explanation:
17x +x to the second power
We want to use the Substitution method to solve
7x - 2y = 1 (1)
x - 2y = 1 (2)
From equation (1), obtain
2y = 7x - 1 (3)
Substitute (3) into (2).
x - (7x - 1) = 1
-6x + 1 = 1
-6x = 0
x = 0
From (3), obtain
2y = 7*0 - 1 = -1
y = -1/2
Answer: (0, -1/2) or x=0, y= -1/2.
Answer:
.
Step-by-step explanation:
We have been given an equation . We are supposed to solve our given equation step by step.
Step 1: Use the distributive property.
Step 2: Combine like terms.
Step 3: Use subtraction property of equality:
Step 4: Use the division property of equality:
Therefore, the solution of our given equation is .